China's African revolution - Hutchison, Alan. (London : Hutchinson, 1975)
Monograph on international relations and economic relations between China and Africa, with particular reference to the role of China in extending development aid - covers Chinese foreign policy trends, political aspects of the Chinese role in africa, etc. Bibliography pp. 301 and 302, illustrations and references.
Includes bibliographical references (pages 301-302) and index.
Keywords: International relations; economic relations; role of China; development aid; foreign policy; trend; political aspect; relations internationales; Africa -- Relations -- China; China -- Relations -- Africa; bibliography; illustration; reference; illustration